ECONOMY AND PRICE DYNAMICS: MANAGING INFLATION UNDER ECONOMIC UNCERTAINTY - Babayeva Sabinabonu Davronbek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the multifaceted nature of inflation and its macroeconomic  implications.  It  identifies  and  analyzes  the  primary  factors contributing  to  inflation,  including  monetary  expansion,  fiscal  policy,  demand  and supply  imbalances,  production  costs,  exchange  rate  volatility,  and  inflation expectations.  The  study  emphasizes  how  these  determinants  interact  within  the economic  system  and  evaluates  the  role  of  central  banks  and  governments  in maintaining price stability. By considering both domestic and international contexts, the  paper  highlights  the  importance  of  a  coordinated  policy  approach  to  ensure sustainable economic development and macroeconomic equilibrium.